1996
DOI: 10.1002/(sici)1520-636x(1996)8:1<39::aid-chir9>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric composition and prevalence of some bicyclic monoterpenoids in amber

Abstract: Among the more prevalent chiral monoterpenoid compounds in conifers are α‐pinene, β‐pinene, and smaller amounts of camphene and limonene. The most prevalent chiral monoterpenoid compounds in fossilized resin (referred to as amber in this paper) appear to be borneol, isoborneol, and camphene. Most of these compounds have easily measured enantiomeric excesses. The borneol and isoborneol in some amber samples have pronounced enantiomeric excesses despite the fact that they are tens of millions of years old. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…7E and 8C). GC-MS has proven to be effective in resolving stereoisomers of many terpenoid compounds (Armstrong et al, 1996;Huang and Armstrong, 2009). Because the peak observed in assays combining SrCPS and SrKSL has a different retention time with a similar mass spectrum as ent-copalol, we postulate that the unidentified compound could be a stereoisomer of ent-copalol.…”
Section: Rna-seq Data Of Stevia Leaf Tissues Distinguished Gene Membementioning
confidence: 96%
“…7E and 8C). GC-MS has proven to be effective in resolving stereoisomers of many terpenoid compounds (Armstrong et al, 1996;Huang and Armstrong, 2009). Because the peak observed in assays combining SrCPS and SrKSL has a different retention time with a similar mass spectrum as ent-copalol, we postulate that the unidentified compound could be a stereoisomer of ent-copalol.…”
Section: Rna-seq Data Of Stevia Leaf Tissues Distinguished Gene Membementioning
confidence: 96%
“…Stereochemical analysis also can be of importance in 6.C. CONTRIBUTIONS BY OTHER CHROMATOGRAPHERS geochemistry [5,6,24,25], geochronology [26], biochemistry, and in some areas of materials science [7].…”
Section: C6 the Enantiomeric Separations Revolution (Daniel W Armentioning
confidence: 99%
“…As in chromatography, considerable present research is now focusing on an assembly of macrocyclic building blocks to produce supramolecular structures with desired properties, including ligand-exchange processes, cyclodextrin phase arrays, enantioselective and molecular recognition as given in 13 papers on supramolecular chemistry at the 35th Midwest Regional Meeting of the American Chemical Society, Oct. [25][26][27]2000 in St. Louis, MO [2]. CE, capillary electrochromatography (CEC), and ultra-high-pressure liquid chromatography (UHPLC), which allows the use of very small particles generating plate numbers of 100,000 -200,000 or more.…”
Section: C8 Sephadex Derivatives For Extraction and Sample Preparmentioning
confidence: 99%
“…The separation of enantiomers, (+)‐ and (−)‐ borneol as well as (+)‐ and (−)‐isoborneol by chiral gas chromatography (GC) was reported by us and other groups previously . Generally speaking, the main drawbacks of chiral column are high cost and durability.…”
Section: Introductionmentioning
confidence: 99%
“…10 The separation of enantiomers, (+)-and (−)-borneol as well as (+)-and (−)-isoborneol by chiral gas chromatography (GC) was reported by us and other groups previously. [10][11][12][13][14] Generally speaking, the main drawbacks of chiral column are high cost and durability. Our unpublished results also showed that applications of samples extracted from fermentation media or herbal ointment complexes usually led to irreversible damage of the βcyclodextrin-based chiral GC column after several runs.…”
Section: Introductionmentioning
confidence: 99%